On the formation of “Fish-scale” morphology with curved grain interfacial microstructures during selective laser melting of dissimilar alloys - Yao, Liming (2022)
For successful fabrication of components using additive manufacturing techniques such as powder bed fusion (PBF), directed energy deposition, and laser cladding of an alloy on to a substrate of a dissimilar one, an interpenetrating interface morphology is essential for a good interface strength. The physical mechanisms behind the formation of different solidified interface morphologies after single track laser PBF of Inconel 718 powders on to the 316L austenitic stainless stress substrate were investigated by recourse to numerical simulations, which combine micron-scale fluid dynamics and solidification protocols with nanosecond-level thermal diffusion processes. These were complemented with parametric experiments to verify the simulations. Results show that an interface with the “fish scale” morphology can occur under certain combinations of process parameters, and because of the combined actions of recoil pressure, Marangoni forces, surface tension and melt pool shape. Three distinct morphologies that depend on the melt pool width and depth are identified and the interfacial areas for each of them are computed. The influence of the processing conditions that not only dictate the geometric parameters of the melt pool but also the degree of alloying and the resulting grain morphology within the interface microstructure were elucidated.